Middle East Respiratory Syndrome Coronavirus in Bats, Saudi Arabia - Memish, Ziad A. (Centers for Disease Control and Prevention, 2013)
The source of human infection with Middle East respiratory syndrome coronavirus remains unknown. Molecular investigation indicated that bats in Saudi Arabia are infected with several alphacoronaviruses and betacoronaviruses. Virus from 1 bat showed 100% nucleotide identity to virus from the human index case-patient. Bats might play a role in human infection.